PToolkit Prototype: Mixed Fidelity for Design Idea Transformation - Zuhana Saidin, Aeni; Shaari, Nassiriah; Alwi, Asmidah (International Journal of Engineering and Technology, 2018)
This paper describes about the design and development of PToolkit prototype.  We used both low and high fidelity prototype techniques for development of PToolkit prototype interactive application with expert user collaboration in the design iterative phases.  Low fidelity prototype enables exploration for the general layout and information contents, whereas high fidelity prototype allows experimentation in providing experience for intended context and target user group.  Both techniques has proved provide experiences in design context, thus allows an early reflection and design transformation.